State Bar Annual Meeting in Monterey - Watkins, Howard::::::::: (1988)
Fresno County Bar Delegation Dinner: Brad Hill, Brenda Hill, Thomas Tusan, Diana Tusan, Jennifer French, Dana French, Sandra Snyder-Hylton, Stephanie Oliver, Robert Oliver, Howard Watkins, Debra Kazanjian, Donald Fischbach, Karen Burt, John Misserlian, Dale Reid, Jack Hames, Tara Sullivan Hames, and Judy Soley